A regulação transnacional de patentes e o acesso à saúde na sociedade global: compatibilidade entre o direito à propriedade intelectual e o direito à saúde - Benetti, Daniela Vanila Nakalski (Universidade do Vale do Rio do Sinos, 2007)
The juridical system in the modernity identifies the goods produced intellectually as private property modality, and since then, the patent has been the instrument rationally created to protect an invention. However the patent is a paradoxical instrument, because it deals with the private appropriation of goods of collective nature. At the end of the 20th century the intellectual rights of properties were re-addressed to WTO’s scope by the TRIPS Agreement. When dealing with the intellectual rights of properties in the scope of the international commerce the WTO’s state-members, carrying into account the serious global sanitary problems, as AIDS legalized the Doha’s Declaration as a form of supporting the public health regarding the access to medication. It sustains that both systems, sanitary and patent, are essences to the global society, however the very society puts itself in risk every time it opts in standardize the patent monopoly for all the research sectors. To guarantee the access to the medicatio
Keywords: acesso à saúde; licença compulsória; sistema transnacional de patentes; sociedade global; direito à saúde; access to health; compulsory license; global society; transnational system of patents; right to health; Ciências Sociais Aplicadas